06.14 Proteasome inhibition with bortezomib in sle promotes therapeutically relevant depletion of short- and long-lived plasma cells but does not prevent their regeneration. (1st March 2017) - Alexander, Tobias; Cheng, Qingyu; Klotsche, Jens; Hoyer, Bimba; Taddeo, Adriano; Waka, Aderajew; Kühl, Anja A.; Burmester, Gerd R; Radbruch, Andreas; Hiepe, Falk
Abstract : Objectives: We previously identified long-lived plasma cells (PCs) are an essential component of the pathogenic immunologic memory, which is resistant to immunosuppressive and B cell depleting therapies and contributes to the chronicity of SLE. We recently demonstrated that their targeting with the proteasome inhibitor bortezomib resulted in therapeutically relevant plasma cell depletion in refractory cases of SLE. Here we investigated in detail the cellular and serologic responses of bortezomib treatment. Methods: Eight patients received a median of two 21-day cycles of intravenous bortezomib 1.3mg/m 2 as induction therapy for active SLE. Disease activity was assessed using the SLEDAI-2K score. Serum concentrations of anti-double-stranded DNA (anti-dsDNA), vaccine-induced antibodies and BAFF levels were monitored. Flow cytometry was performed to analyse peripheral blood B cells, T cells and PCs and Siglec-1 expression on monocytes as surrogate marker for type-I interferon (IFN). Results: Upon proteasome inhibition, serum levels for anti-double-stranded (ds)DNA (~60%) and vaccine-induced antibodies for Measels, Mumps, TT (~30%) significantly declined, complement levels and serum BAFF levels significantly increased and SLEDAI significantly decreased (p=0.014). The level of bone marrow PCs decreased by 50%, affecting both CD19 + and CD19 - CD138/CD38 expressing PCs. While number and phenotype of peripheral blood T- and B cells remained unaffected, proteasome inhibition was associated with a significant depletion of HLA-DR + (p=0.024), HLA-DR - (p=0.038) and IgA + (p=0.032) PCs, but their regeneration was fast. Within ten days from the last bortezomib injection, their numbers significantly increased (beta=2.1; 95% CI: 0.5, 3.7; p=0.012), an effect that was more pronounced in HLA-DR + short-lived than in HLA-DR - long-lived PCs. Overall, the magnitude of increase over time did not significantly decrease. Siglec-1 expression on monocytes significantly declined. Conclusions: These findings identify proteasome inhibitors as a promising novel treatment option for patients with refractory SLE by targeting short- and long-lived PCs and type I IFN activity. Bortezomib efficiently induces short-term remissions but would require additional B cell directed treatment approaches to inhibit PC regeneration from their precursors for sustained efficacy.